Effects of Gamma Irradiation on Ruminal Degradation of Samurai 1 Sweet Sorghum Bagasse - T. Wahyono; N. Lelananingtyas; S Sihono (PPIKSN-BATAN, 2017)
The purpose of this study was to investigate the influence of gamma irradiation on dry matter, organic matter, and neutral detergent fiber degradability of Samurai 1 sweet sorghum bagasse, to facilitate its utilization in ruminant diets. Sorghum bagasse was obtained from Samurai 1 sorghum stem by-product after juice extraction. Gamma irradiation was carried out in a cobalt-60 irradiator in the Center for the Application of Isotopes and Radiation. Two polyethylene packages of samples were irradiated in gamma cell (Co-60) at doses of 50 and 100 kGy in the presence of air. Treatments were untreated/unirradiated and 50- and 100-kGy gamma irradiation. Sample were incubated in the rumen for periods of 0, 8, 24, 48, and 72 h with in sacco method. The observed parameters were the degradations of dry matter (DM), organic matter (OM), and neutral detergent fiber (NDF). DM, OM and NDF degradation characteristics were also observed. DM degradation of 50 kGy irradiation dose started higher than untreated samples after 24 hours incubation while OM degradation started higher than untreated samples after 48 hours incubation. DM and OM degradation of 100 kGy irradiation started higher than untreated after 8 hours incubation. Gamma irradiation treatment of 50 kGy and 100 kGy could increase NDF degradation on 8 to 72 hours incubation. Irradiation was also capable to increase NDF degradation rate (c fraction) and ruminal effective degradation (ED) value on Samurai 1 sweet sorghum bagasse. Gamma Irradiation could break down the lignocellulose materials, break β 1,4 branch chain of cellulose and make it easily digested for rumen bacteria. The best dose of gamma irradiation for processing Samurai 1 sweet sorghum bagasse as a fiber source for ruminants was 100 kGy.Received: 10 December 2015; Revised: 10 October 2016; Accepted: 10 October 2016